Non-alcoholic fatty liver disease: Patient profiles and key contributing factors - Mustika, Syifa; Rosita, Firdha; Sagala, Ida; Satiti, Ika (PT. DEKA RESEARCH INSTITUTE, 2025)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) is a growing global health concern, strongly associated with obesity, metabolic syndrome, and cardiovascular diseases. Recognizing the key risk factors is essential for early detection and prevention. OBJECTIVES: This study aims to examine patient profiles and identify the primary contributing factors to NAFLD. METHODS: This cross-sectional study was conducted in the Gastroenterohepatology Division of Dr. Saiful Anwar Hospital, Malang, from May to October 2022. A total of 31 patients diagnosed with NAFLD based on abdominal ultrasound findings were included. Data were collected through medical history assessments, physical examinations, laboratory tests, and transient elastography. Multivariate logistic regression analysis was performed using SPSS 25 software. RESULTS: The findings revealed that age (p = 0.029), body mass index (BMI) ≥23 kg/m² (p < 0.001), abdominal circumference exceeding normal limits (p < 0.001), and dyslipidemia (p < 0.001) were significantly associated with NAFLD. However, blood pressure, gender, fasting blood sugar, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) did not exhibit significant associations (p > 0.05). CONCLUSION: The study identified age, obesity, abdominal circumference, and dyslipidemia as the main contributing factors to NAFLD. Early detection and targeted intervention for metabolic risk factors are crucial in preventing disease progression.